2011
DOI: 10.1128/jvi.05608-11
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Regulatory T Cells Accompanies Increased Immune Activation in Rectal Mucosae of HIV-Positive Noncontrollers

Abstract: Gut-associated lymphoid tissue (GALT) is a major site of HIV replication and CD4؉ T cell depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
94
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 99 publications
12
94
0
1
Order By: Relevance
“…These individuals were compared to progressors (VL > 10,000, CD4 decline below 500 cells/ll) and controllers (VL < 1,000, infected > 5 years). A previous study from our group reported on mucosal Treg and immune activation in HIV controllers and progressor subjects, who were also used as comparison groups for this study 25 ; however, data and analysis of VSP subjects were not presented in the earlier report. Subjects were recruited at the UC Davis Medical Center, Sacramento, CA or San Francisco General Hospital, UC San Francisco (UCSF).…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…These individuals were compared to progressors (VL > 10,000, CD4 decline below 500 cells/ll) and controllers (VL < 1,000, infected > 5 years). A previous study from our group reported on mucosal Treg and immune activation in HIV controllers and progressor subjects, who were also used as comparison groups for this study 25 ; however, data and analysis of VSP subjects were not presented in the earlier report. Subjects were recruited at the UC Davis Medical Center, Sacramento, CA or San Francisco General Hospital, UC San Francisco (UCSF).…”
mentioning
confidence: 92%
“…Rectal biopsies were obtained by flexible sigmoidoscopy 26 and mucosal leukocytes isolated using collagenase and mechanical disruption. 25 PBMCs and rectal cells were stained with anti-CD3 (clone UCHT1; BD Pharmingen), anti-CD4 (SFCI12T4D11, Beckman Coulter, Brea, CA, or L200, BD Pharmingen), anti-CD8 (SK1 or 3B5, Invitrogen), anti-CD25 (M-A251, BD Pharmingen), anti-CD127 (hIL-7R-M21, BD Pharmingen), anti-CD38 (HIT2, BD Pharmingen), antiprogrammed-death-receptor 1 (PD-1) (eBioJ105, eBioscience), and Live/Dead Fixable Aqua dead cell stain (Invitrogen, Carlsbad, CA), followed by intracellular staining with anti-FOXP3 (PCH101, eBioscience) using the FOXP3 Staining Buffer Set (eBioscience, San Diego, CA). After acquisition on an LSRII flow cytometer (BD Pharmingen), data were analyzed using FlowJo software (Tree-Star Inc., Ashland, OR).…”
mentioning
confidence: 99%
See 3 more Smart Citations